Individualization program training in freestyle wrestling - Latyshev, S. (Physical Education of Students, 2013)
The purpose of the study - the development and verification of the effectiveness of the program individualization of training fighters. The program aims at the establishment of individual style confrontation wrestlers. The experiment involved two groups of fighters: experimental (21 fighter) and control group (30 wrestlers), aged 16-17 years. Duration of the experiment was 2.5 years. Model profiles of each of the typical style of confrontation included anthropometry, physical and psychological indicators. The coefficients of correlation between the profile of preparedness wrestler and model profiles of each of the typical style of warfare. The maximum correlation coefficient showed a predisposition to certain typical fighter style confrontation. Found that most of the fighters have a moderate degree of conformity to one of the typical styles of warfare.